Efeitos do extrato aquoso de Zingiber officinale Roscoe na endometriose induzida em ratas wistar - MORAIS FILHO, José Meneses de (2020)
Introduction: Endometriosis is a chronic inflammatory disease characterized by the development and growth of stroma and glands of endometrial tissue outside the uterine cavity, may affect any organ and when located in the abdomen of women is associated with pain and subfertility and in some cases with substantial reduction in quality of life. The treatment aims at reducing pain, the possibility of fertility and improving quality of life, and may be clinical or / and surgical, which reduces the focuses of the disease and symptoms, inherent to the affected organs, but without definitive cure. New treatment strategies have been researched such as the use of plant extracts, among them Zingiber officinale Roscoe (ginger), which have anti-oxidant action and immunomodulatory effect, reducing the production of pro-inflammatory cytokines, the volume of ectopic foci and atrophying the implants. Objective: To analyze macroscopic and microscopic aspects of endometriotic tissues and to evaluate TNF- and IL-6 in the peritoneal lavage of rats with induced endometriosis that received ginger orally. Method: Randomized clinical trial of 20 virgin Wistar rats (Rattus novergicus albinus). Endometriosis was induced in the animals and after 21 days a new surgery was performed to measure the volume of ectopic tissue and the animals were randomly divided into two groups: the control group (n=8) received 0.9% sodium chloride solution by gavage and the ginger group (n=8) received 500 mg/kg of Zingiber officinale Roscoe extract by gavage, both for 14 days. After this period the animals were sacrificed and the liquid from the peritoneal lavage was collected, the volumes of the lesions and the excision of the endometriotic foci were measured for histological analysis. Results: The final mean volumes after the intervention were higher in the control group (120.93 mm3 ± 78.91) than in the ginger group (40.50 mm3 ± 19.57), with significant statistical difference (p = 0.01). The focus of endometriosis increased more in the control group (75.81 mm3 ± 58.95) than in the ginger group (2.07 mm3 ± 18.87) (p = 0.004) when comparing the size of the lesions on euthanasia day. There was no difference in the TNF- dosage in the control group (59.26 pg/ml ± 12.07) in relation to the ginger group (55.00 pg/ml ± 13.49) (p = 0.51), as well as no difference in the IL-6 dosage in the control group (183.43 ± 13.90) in relation to the ginger group (205.18 ± 34.81) (p = 0.12). The degree of atrophy of the lesions was higher in the ginger group (1 ± 0.92) than in the control group (2.25 ± 1.16) (p = 0.03). Conclusions: The ginger extract reduced and atrophied the volumes of the autotransplanted endometriosis foci but did not reduce IL-6 and TNF-α in the peritoneal lavage fluid.